2015
DOI: 10.1007/s10120-015-0475-2
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a DNA methylation marker to evaluate cancer cell fraction in gastric cancer

Abstract: Background Tumor samples are unavoidably contaminated with coexisting normal cells. Here, we aimed to establish a DNA methylation marker to estimate the fraction of gastric cancer (GC) cells in any DNA sample by isolating genomic regions specifically methylated in GC cells. Methods Genome-wide and gene-specific methylation analyses were conducted with an Infinium HumanMethylation450 BeadChip array and by quantitative methylationspecific PCR, respectively. Purified cancer and noncancer cells were prepared by la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
(34 reference statements)
0
18
0
Order By: Relevance
“…In this study, we evaluated the methylation status of three genes together in both tissue and serum samples to improve the sensitivity. According to Zong et al [ 20 ] research, by using an Infinium HumanMethylation 450 BeadChip array, they identified that OSR2, VAV3, and PPFIA3 are barely methylated in normal cells but highly methylated in GC cells. To further assess the clinical value of methylated OSR2, VAV3, and PPFIA3, we first analyzed those genes' methylation status in GC tissue samples or PCHNTs samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we evaluated the methylation status of three genes together in both tissue and serum samples to improve the sensitivity. According to Zong et al [ 20 ] research, by using an Infinium HumanMethylation 450 BeadChip array, they identified that OSR2, VAV3, and PPFIA3 are barely methylated in normal cells but highly methylated in GC cells. To further assess the clinical value of methylated OSR2, VAV3, and PPFIA3, we first analyzed those genes' methylation status in GC tissue samples or PCHNTs samples.…”
Section: Discussionmentioning
confidence: 99%
“…Current microarray technology provides us with an opportunity for high-throughput unbiased methylation analysis of a large number of CpG sites [ 19 ]. By using an Infinium HumanMethylation 450 BeadChip array, Zong and colleagues [ 20 ] identified three genes (OSR2, VAV3, and PPFIA3) that were hypermethylated in GC tissue. Odd-skipped related 2 (OSR2), which contains DNA-binding C2H2-type zinc finger domains in the C-terminal half, plays an important role in cellular quiescence and proliferation under epigenetic regulation [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Illumina Infinium HumanMethylation450 BeadChip array has been used to detect genome-wide DNA methylation profile alterations in cancer [ 14 16 ]. Using this array, we analyzed 26 paired CRC and noncancerous colorectal tissues and found multiple hypermethylated loci in the promoter and exon 1 regions of BEND5 .…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the cancer cell fraction in DNA samples, we previously established a unique method using cancer cell-specific DNA methylation in esophageal squamous cell carcinomas and gastric cancers [9,10]. The method utilizes a panel of a limited number of genes, typically three, specifically methylated in cancer cells and unmethylated in noncancer cells, such as normal epithelial cells, fibroblasts, and blood cells.…”
Section: Introductionmentioning
confidence: 99%